Evaluation of Growth Characteristics and Haematological Indices of Broiler-chicks Fed Raw and Processed Bambara Groundnut Seed as a Component of Poultry Feed - Oloyede, O.B.; Minari, J.B.; Muhammad, N.O. (International Journal of Poultry Science, 2010)
Sixty broiler chicks (day-old) were used in a 4-week feeding experiment to assess the growth response and heamatological variables of broilers-chicks fed raw, roasted and fermented bambara groundnut as a sole source of protein. Soybean based diet served as the control. There were four (4) experimental groups, each made up of five birds in three replicates, allocated to the experimental diets. The results showed that the average final live weight, average weekly weight gain and average feed intake of birds fed fermented bambara groundnut performed better than birds fed roasted bambara groundnut but demonstrated inferiority when compared to the control. Among other organs measured the relative weight of gizzard were significantly (p<0.05) influenced by the dietary treatment. Protein quality as revealed by the haematological parameters, like Haemoglobin (Hb), Packed Cell Volume (PCV) and Red Blood Cell (RBC) levels indicated that fermented based diet fed to the birds performed better than but demonstrated inferiority when compare with the soybean based diet. However, the results showed that raw bambara groundnut based diet has a high protein quality when compared with the control diet. The use of bambara groundnut therefore in the feeding of broilers in the developing countries if properly harnessed and processed can make poultry production affordable.